2008
DOI: 10.1245/s10434-008-0245-z
|View full text |Cite
|
Sign up to set email alerts
|

Breast Specimen Orientation

Abstract: Lumpectomy specimens are commonly divided into six sides: superficial, deep, superior, inferior, medial, and lateral. Orienting stitches are placed on the specimen during surgery to allow reorientation by pathology. Despite those efforts, specimen disorientation may occur. The aim of this study was to assess the correlation in orientation between surgeons and pathologists. Lumpectomy specimens were routinely oriented. An additional Prolene suture was randomly placed by the surgeon on one side to be localized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…9,17,18 Shave specimens, which were employed to reduce pathology disorientation and standardize specimen handling procedures, were evaluated with the handheld imaging probe on the final margin (i.e., the true margin or new margin). 19 At least four images per specimen were acquired in regions most suspicious for disease, as identified using the image data. Specimens were marked with sutures or ink to indicate final margin orientation before submission to pathology for standard-of-care gross and histology evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…9,17,18 Shave specimens, which were employed to reduce pathology disorientation and standardize specimen handling procedures, were evaluated with the handheld imaging probe on the final margin (i.e., the true margin or new margin). 19 At least four images per specimen were acquired in regions most suspicious for disease, as identified using the image data. Specimens were marked with sutures or ink to indicate final margin orientation before submission to pathology for standard-of-care gross and histology evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…(4) If additional tissue was excised, the surgeon used the handheld OCT probe to image the new aspect(s) of the resection bed. (5) All excised tissue specimens were evaluated with the handheld OCT probe in the operating room by the research staff. (6) Specimens were marked with dye at the OCT imaging sites for correlation and returned to the operating room staff for routine histopathological examination by a board-certified pathologist.…”
Section: Methodsmentioning
confidence: 99%
“…(4) It is also challenging to spatially correlate the analyzed regions on excised specimens with the corresponding locations in the resection bed. (5) As the currently available tools are limited, there is a compelling need to improve upon these existing intraoperative methods to enable real-time microscopic detection of residual disease both within the resection bed and on resected specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Marking sutures have traditionally been placed on 2 or more of the 6 surfaces of a lumpectomy specimen by the surgeon in the operating room, followed by inking of all 6 margins done by the pathologist in the lab. Molina et al demonstrated that with 2 marking sutures placed by the surgeon, there was a 20% rate of discordance between surgeon and pathologist interpretation of the margins in specimens larger than 20 square cm [65]. In smaller specimens less than 20 square cm, the discordance was as high as 78%.…”
Section: Pathologic Assessmentmentioning
confidence: 99%